Comparing health status, disability, and access to care in older and younger inmates in the New South Wales corrections system. Issue 2 (11th March 2019) - Field, Courtney; Archer, Vicki
Abstract : Purpose: The purpose of this paper is to compare the rates of chronic illness, disability and access to care between older and younger inmates who took part in a large epidemiological study in New South Wales, Australia. Design/methodology/approach: Data are presented from a cross-sectional study based on a sample of inmates from correctional sites in NSW. The inclusion of results here was guided by the literature with regard to their relevance to older people, and older inmates in particular. Findings: Results indicate that a higher proportion of older inmates suffer a range of chronic illnesses, with prevalence often many times higher than that of younger inmates. Older inmates are more likely to be classified as disabled and have a disability which impacts their mobility. Older inmates also reported accessing medical services in prison more recently than younger inmates and were more likely to have seen both nurses and general practitioners. Practical implications: Older inmates appear to be considerably more resource intensive than younger inmates. The increasing proportion of inmates who are classified as older thus poses a pressing challenge to those working in the carceral space and, in particular, those responsible for providing healthcare to incarcerated people. Originality/value: The impact of aging prisoners on resource demand has yet to be effectively measured. This study provides an important first step towards that goal.